Explaining female and male entrepreneurship at the country level - Ingrid Verheul; André van Stel; Roy Thurik (Max Planck Institute of Economics, 2005)
Using Global Entrepreneurship Monitor data for 29 countries this study investigates the (differential) impact of several factors on female and male entrepreneurship at the country level. These factors are derived from three streams of literature, including that on entrepreneurship in general, on female labor force participation and on female entrepreneurship. The paper deals with the methodological aspects of investigating (female) entrepreneurship by distinguishing between two measures of female entrepreneurship: the number of female entrepreneurs and the share of women in the total number of entrepreneurs. The first measure is used to investigate whether variables have an impact on entrepreneurship in general (influencing both the number of female and male entrepreneurs). The second measure is used to investigate whether factors have a differential relative impact on female and male entrepreneurship, i.e., whether they influence the diversity or gender composition of entrepreneurship. Findings indicate that - by and large - female and male entrepreneurial activity rates are influenced by the same factors and in the same direction. However, for some factors (e.g., unemployment, life satisfaction) we find a differential impact on female and male entrepreneurship. The present study also shows that the factors influencing the number of female entrepreneurs may be different from those influencing the share of female entrepreneurs. In this light it is important that governments are aware of what they want to accomplish (i.e., do they want to stimulate the number of female entrepreneurs or the gender composition of entrepreneurship) to be able to select appropriate policy measures.
Keywords: M13; H10; J16; J23; 330; entrepreneurship; gender; determinants of entrepreneurship; Auslandsinvestition; Wissenstransfer; Entwicklung; Entrepreneurship-Ansatz; Vergleich; Irland; Ungarn